Autophagy is a promising process for linking inflammation and redox homeostasis in Down syndrome - Ma, Xuehai; Li, Weimin; Ma, Jun; Han, Zhongcheng; Deng, Shoulong; Wang, Sutian (Frontiers in Pharmacology, 2024)
Trisomy 21, characterized by the presence of an additional chromosome 21, leads to a set of clinical features commonly referred to as Down syndrome (DS). The pathological phenotypes observed in DS are caused by a combination of factors, such as mitochondrial dysfunction, neuroinflammation, oxidative stress, disrupted metabolic patterns, and changes in protein homeostasis and signal transduction, and these factors collectively induce neurological alterations. In DS, the triplication of chromosome 21 and the micronuclei arising from the missegregation of chromosomes are closely associated with inflammation and the development of redox imbalance.Autophagy, an essential biological process that affects cellular homeostasis, is a powerful tool to facilitate the degradation of redundant or dysfunctional cytoplasmic components, thereby enabling the recycling of their constituents. Targeting the autophagy process has been suggested as a promising method to balance intracellular inflammation and oxidative stress and improve mitochondrial dysfunction. In this review, we summarize the role of autophagy in regulating inflammation and redox homeostasis in DS and discuss their crosslinks. A comprehensive elucidation of the roles of autophagy in DS offers novel insights for the development of therapeutic strategies aimed at aneuploidy-associated diseases.